Pengaruh Proses Rekrutmen, Seleksi, Dan Training Terhadap Kinerja Karyawan - Zahurotul Bella Maharani; Agus Widarko; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to reveal and analyze the process of recruitment, selection, and training on the performance of employees. Finding out the direct impact of the recruitment process, selection, and training on the performance of production employees. Finding out the indirect impact of the recruitment process, selection, and training on the performance of production employees in cigarette factory Redi Berka Abadi. The research method used is quantitative research with the type of research is Explanatory Research. In this study, the sampling technique used was Probability Sampling with Simple Random Sampling. The research population is all production employees in cigarette factory Redi Berka Abadi with a total of 100 people. While the sample used in this study was 50 people.The result of the research shows that the recruitment process had no impact and was not significant in employees' performance. The selection process does not affect and is not significant in employees' performance. While the training process has a significant effect on employees' performance so that if the company gives training to employees more often, it means that employee skills will increase and employees' performance increases as well.Keywords: recruitment process, selection process, training process, employees’ performance